Identification of lectin counter-receptors on cell membranes by proximity labeling - Wu, Gang (Glycobiology, 2017)
Lectin–glycan interactions play important roles in many biological systems, but the nature of glycoprotein counter-receptors expressed on cell membranes is often poorly understood. To help overcome this problem, we developed a method based on proximity labeling technology. Using a peroxidase-coupled lectin, addition of H(2)O(2) and tyramide-biotin substrates leads to generation of short-range biotin radicals that biotinylate proteins in the immediate vicinity of the bound lectin, which can subsequently be identified. As a proof-of-principle, sialoadhesin-horseradish peroxidase-human IgG1 Fc recombinant protein constructs were precomplexed with anti-Fc antibodies, bound to human erythrocytes and reacted with H(2)O(2) and tyramide-SS-biotin. The erythrocyte membrane protein with strongest biotinylation was identified as glycophorin A, in agreement with early studies using lectin overlay and reglycosylation approaches. As a further test of the method, the plant lectin MAL II was conjugated with horseradish peroxidase and used in proximity labeling of human erythrocytes. Glycophorin A was again selectively labeled, which is consistent with previous reports that MAL II has high affinity for glycophorin. This method could be applied to other lectins to identify their membrane counter-receptors.